2013 IEEE International Conference on Acoustics, Speech and Signal Processing 2013
DOI: 10.1109/icassp.2013.6638464
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficient source localization on a Manhattan grid wireless sensor network

Abstract: For wireless sensor networks, many decentralized algorithms have been developed to address the problem of locating a source that emits acoustic or electromagnetic waves based on received signal strength. Among the motivations for decentralized algorithms is that they reduce the number of transmissions between sensors, thereby increasing sensor battery life. Whereas most such algorithms are designed for arbitrary sensor placements, such as random placements, this paper focuses on applications that permit a choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Previously, it was found that Manhattan grid sensor deployments allow for a significant reduction in communication energy over random or lattice deployments with only a modest loss in error performance for the problem of decentralized RSS localization [8]. This new work provides analytical and experimental evidence for an identical performance-energy tradeoff, but in the context of a centralized RSS localization problem.…”
Section: Conclusion and Acknowledgmentsmentioning
confidence: 87%
See 2 more Smart Citations
“…Previously, it was found that Manhattan grid sensor deployments allow for a significant reduction in communication energy over random or lattice deployments with only a modest loss in error performance for the problem of decentralized RSS localization [8]. This new work provides analytical and experimental evidence for an identical performance-energy tradeoff, but in the context of a centralized RSS localization problem.…”
Section: Conclusion and Acknowledgmentsmentioning
confidence: 87%
“…In particular, our results suggest that there may be a fundamental advantage of honeycomb networks over other networks in terms of energy efficiency, which should be further investigated in future research. More efficient, decentralized algorithms for solving the source localization problem in cutset networks, such as the algorithm in [8], should also be investigated. Finally, future work should consider communication issues in cutset networks, such as scheduling, routing, and bounds on network throughput.…”
Section: Conclusion and Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that there are energy-saving advantages to placing wireless sensor networks in a Manhattan geometry; specifically, Manhattan grid geometries allow sensors to be placed closer together than random or lattice networks at the same density, allowing for lower-energy communication between sensors. The authors in [1] proposed the Midpoint Algorithm for solving a source localization problem from data collected from Manhattan wireless sensor networks. Both this algorithm and the Manhattan grid geometry offered significant energy savings over other distributed localization algorithms on random/lattice networks.…”
Section: Introductionmentioning
confidence: 99%
“…If sensors are deployed on a Manhattan grid, as opposed to random placement, then the energy costs of data transmission tends tend to be much smaller [6]. Such "Manhattan networks" can be used to efficiently solve the problem of RSS-based source localization [7].…”
Section: Introductionmentioning
confidence: 99%